Evaluation of Immunosuppressive Therapy Use for Tracheal Transplantation with Trachea-Mimetic Bellows Scaffolds in a Rabbit Model. (26th October 2017) - Lee, Jae Yeon; Park, Jeong Hun; Son, Soo Jin; Han, Mina; Kim, Gonhyung; Kang, Seong Soo; Choi, Seok Hwa; Cho, Dong-Woo
Abstract : The objective of this study was to evaluate the use of immunosuppressive therapy with high-dose cyclosporine, high-dose azathioprine, and a combination of low-dose cyclosporine and azathioprine after tracheal reconstruction by using a trachea-mimetic graft of polycaprolactone (PCL) bellows-type scaffold in a rabbit model. Twenty-four healthy New Zealand white rabbits were used in the study. All underwent circumferential tracheal replacement using tissue-engineered tracheal graft, prepared from PCL bellows scaffold reinforced with silicone ring, collagen hydrogel, and human turbinate mesenchymal stromal cell (hTMSC) sheets. The control group (Group 1) received no medication. The three experimental groups were given daily cyclosporine intramuscular doses of 10 mg/kg (Group 2), azathioprine oral doses of 5 mg/kg (Group 3), and azathioprine oral doses of 2.5 mg/kg plus cyclosporine intramuscular doses of 5 mg/kg (Group 4) for 4 weeks or until death. Group 1 had longer survival times compared to Group 2 or Group 3. Each group except for Group 1 experienced decreases in amount of nutrition and weight loss. In addition, compared with the other groups, Group 2 had significantly increased serum interleukin-2 and interferon-γ levels 7 days after transplantation. The results of this study showed that the administration of cyclosporine and/or azathioprine after tracheal transplantation had no beneficial effects. Furthermore, the administration of cyclosporine had side effects, including extreme weight loss, respiratory distress, and diarrhea. Therefore, cyclosporine and azathioprine avoidance may be recommended for tracheal reconstruction using a native trachea-mimetic graft of PCL bellows-type scaffold in a rabbit model.